Confocal endomicroscopy diagnostic criteria for early signet-ring cell carcinoma in hereditary diffuse gastric cancer - Pilonis, Nastazja D.; O’Donovan, Maria; Richardson, Susan; Fitzgerald, Rebecca C.; di Pietro, Massimiliano (BMC gastroenterology, 2023)
Background Recognition of early signet-ring cell carcinoma (SRCC) in patients with hereditary diffuse gastric cancer (HDGC) undergoing endoscopic surveillance is challenging. We hypothesized that probe-based confocal laser endomicroscopy (pCLE) might help diagnose early cancerous lesions in the context of HDGC. The aim of this study was to identify pCLE diagnostic criteria for early SRCC. Methods Patients with HDGC syndrome were prospectively recruited and pCLE assessment was performed on areas suspicious for early SRCC and control regions during an endoscopic surveillance procedure. Targeted biopsies were taken for gold standard histologic assessment. In Phase I two investigators assessed video sequences off-line to identify pCLE features related to SRCC. In Phase II pCLE diagnostic criteria were evaluated in an independent video set by the investigators blinded to the histologic diagnosis. Sensitivity, specificity, accuracy, and interobserver agreement were calculated. Results Forty-two video sequences from 16 HDGC patients were included in Phase I. Four pCLE patterns associated to SRCC histologic features were identified: (A) glands with attenuated margins, (B) glands with spiculated or irregular shape, (C) heterogenous granular stroma with sparse glands, (D) enlarged vessels with tortuous shape. In Phase II, 38 video sequences from 15 patients were assessed. Criteria A and B and C had the highest diagnostic accuracy, with a κ for interobserver agreement ranging from 0.153 to 0.565. A panel comprising these 3 criteria with a cut-off of at least one positive criterion had a sensitivity of 80.9% (95%CI:58.1—94.5%) and a specificity of 70.6% (95%CI:44.0—89.7%) for a diagnosis of SRCC. Conclusions We have generated and validated off-line pCLE criteria for early SRCC. Future real-time validation of these criteria is required.